2020
DOI: 10.1073/pnas.1908003117
|View full text |Cite
|
Sign up to set email alerts
|

RAP80 and BRCA1 PARsylation protect chromosome integrity by preventing retention of BRCA1-B/C complexes in DNA repair foci

Abstract: BRCA1 promotes error-free, homologous recombination-mediated repair (HRR) of DNA double-stranded breaks (DSBs). When excessive and uncontrolled, BRCA1 HRR activity promotes illegitimate recombination and genome disorder. We and others have observed that the BRCA1-associated protein RAP80 recruits BRCA1 to postdamage nuclear foci, and these chromatin structures then restrict the amplitude of BRCA1-driven HRR. What remains unclear is how this process is regulated. Here we report that both BRCA1 poly-ADP ribosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Thus, it has been proposed that the BRCA1-ABRAXAS-RAP80 (BRCA1-A) complex is responsible for localizing PALB2 to DSBs 6 . However, several reports have demonstrated that the BRCA1-RAP80 association reduces cellular HR activity 7 , 8 . Moreover, RAP80 depletion was shown to have little effect on RAD51 foci formation 7 , making the role of RAP80-ABRAXAS in recruiting BRCA1-P ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been proposed that the BRCA1-ABRAXAS-RAP80 (BRCA1-A) complex is responsible for localizing PALB2 to DSBs 6 . However, several reports have demonstrated that the BRCA1-RAP80 association reduces cellular HR activity 7 , 8 . Moreover, RAP80 depletion was shown to have little effect on RAD51 foci formation 7 , making the role of RAP80-ABRAXAS in recruiting BRCA1-P ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its direct role in PARylating sites of DNA damage, PARP has also been documented to PARylate and modify the function of numerous DNA repair proteins, including ATM and BRCA1 [12]. For instance, BRCA1 PARylation prevents dysfunctional HR repair and chromosomal rearrangements [46]. Considering our observation that DFMO affects PARP activity, it is possible that perturbing polyamine levels also alters the activity and function of ATM and BRCA1 by reducing PARylation on these key components of the DNA repair response.…”
Section: Discussionmentioning
confidence: 81%
“…It is worth noting that the NUF2 expression level was positively correlated with the expression levels of CENPI and KNTC1. BRCA1 is a major homologous recombination-mediated repair (HRR) support protein that can work in conjunction with certain chaperone proteins (including RAD51, CTIP, and BRIP1), and it promotes the proper HRR process to regulate the stability of chromosomes [ 64 ]. Its expression level also showed a clear correlation with the expression level of KNTC1.…”
Section: Discussionmentioning
confidence: 99%